Analisis Struktur Hotel Menggunakan Metode Direct Displacement Based Design - Amir, F.; Agung, M.; Sakti, T.; Sutrisno, M. (Tadulako University, 2025)
Palu City is one of the areas prone to earthquakes, as evidenced by the earthquake incident on September 28 2018, buildings in Palu city should be analyzed due to seismic loads and based on structural performance. One of the performance-based analysis methods is the direct displacement based design (DDBD) method. The direct displacement based design method is an seismic analysis method that makes the performance target as an initial reference for seismic load design. The design structure in this paper is a 12-storey hotel structure and located in Palu City, using a special moment resisting frame system, with the quality of the concrete material, f'c = 35 MPa, reinforcement fy = 420 MPa for main reinforcement and 280 MPa for shear reinforcement. The seismic load generated from the DDBD for the X direction is 6986.61 kN and for the Y direction is 6132.91 kN. From the loads acting on the structure, it is found that the safe dimensions of the elements are using column dimensions 800/800, main beam 700/500, and the plate thickness is 140 mm.